Uji Aktivitas Antibakteri Fraksi Etil Asetat Daun Tanaman Bandotan (Ageratum conyzoides L) - Taufan H. Sugara; Tun Tedja Irawadi; Irma Herawati Suprapto; Muhammad Hanafi (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
Utilization of Ageratum conyzoides L. leaf for wound healing and digestion disorders are often associated with its antibacterial activities. However, informastion of this plant as antibacterial agent still limited on the polar and non polar fraction. Therefore, the objective of this study was to identify the antibacterial activity of semipolar fraktion extract of Ageratum conyzoides L. leaves to Staphylococcus aureus and Eschirichia coli. Phytochemical test results showed that the ethyl acetate extract of bandotan leaves contains flavonoids, steroids, p-hydroquinone and terpenoids. Fractionation of ethyl acetate extract with eluent chloroform: methanol (9:1) produced 8 fractions by the number of consecutive yield as much 15,14g; 22,21g; 21,19g; 20,44g; 5,79g; 4,50g; 1,40g; 1,43g; and 0,93g. Overal antibakterial activity result of ethyl acetat extract and fraction 1-8 showed broad-spectrum antibacterial activity with inhibition of belonging to the strong category. The average inhibition of ethyl acetate extracts and fractions 1-8 against S. aureus in a row amounted to 14mm; 12mm; 12,5mm; 15,5mm; 16mm; 12mm; 11,5mm; 10mm; 9,5mm. While, the average inhibition of ethyl acetate extracts and fractions 1-8 against E. coli in a row amounted to 11mm; 11,5mm; 11mm; 11,5mm; 13mm; 14mm; 10.5 mm; 10mm; 9,5mm.